Transanal reinforcement of low rectal anastomosis versus protective ileostomy after total mesorectal excision for rectal cancer. Preliminary results of a randomized clinical trial. (10th May 2021) - Altomare, Donato Francesco; Delrio, Paolo; Shelgyn, Yuri; Rybakov, Evgeny; Vincenti, Leonardo; De Fazio, Michele; Simone, Michele; Graziano, Giusy; Picciariello, Arcangelo
Abstract: Aim: The study aimed to show if transanal reinforcement of the suture line can prevent anastomotic leakage (AL) after rectal cancer surgery, thus avoiding the need for a covering ileostomy. Methods: This is a prospective, multicentre, parallel‐arm randomized controlled equivalence trial. After standard total mesorectal excision, patients with anastomotic line at 1–3 cm from the dentate line were randomized to have transanal suture reinforcement (TAR group) or protective ileostomy (PI group). Results: Twenty‐nine patients had PI, 25 had TAR. The two groups were comparable both for baseline characteristics and intra‐operative aspects. Clinically evident AL occurred in four (16%) and five (17.24%) patients of the TAR and PI group, respectively, resulting in a difference of −1.20% (90% CI −17.93, 15.45), while subclinical AL at proctography was absent in 15 (65.22%) and 13 (50%) patients of the TAR and PI groups, respectively, resulting in a difference of 15% (90% CI −7.74 to 38.17). Conclusion: Preliminary data suggest that transanal reinforcement of the suture line performed in rectal cancer patients with suture line at 1–3 cm from the dentate line carries a similar (even if not equivalent) AL rate to covering ileostomy, suggesting that a covering ileostomy could be avoided in this selected group of patients. This indication needs to be addressed with future larger trials (clinicaltrials.gov ID number NCT02279771).